Effect of Y Concentration on the In Situ Growth Behavior and Corrosion Protection of the MgAlY-LDH Sealing Film on the Anodized Surface of Mg–2Zn–4Y Alloy - Hong, Yuqi; Wu, Liang; Zhang, Xinyi; Zhan, Guoxiang; Chen, Yanning; Yao, Wenhui; Dai, Xu; Wu, Tao; Dai, Xiaowei; Xiang, Jianpeng; Zhou, Yan; Pan, Fusheng (Frontiers in Materials, 2022)
The successful doping of Yttrium (Y) in the Mg-Al layered double hydroxide film (MgAlY-LDHs) is obtained by hydrothermal way on the anodic oxide film of Mg-2Zn-4Y alloys. The composition, morphology and structure of MgAlY-LDHs were characterized by the Fourier transform infrared spectroscopy (FT-IR), X-ray diffractometer (XRD), field-emission scanning electronic microscope (FE-SEM) and energy dispersive spectrometry (EDS) respectively. The electrochemical behavior was observed by polarization curves and electrochemical impedance spectroscopy (EIS). Y ions can be incorporated into the MgAl-LDHs film in a completely isomorphic replacement manner and have the ability to improve the corrosion resistance of the film. Moreover, the ternary LDHs film grown in situ on the Mg-2Zn-4Y alloy provides a high possibility for the corrosion resistance of industrial metals. The schematic representation of electrochemical behavior and the growth mechanism of MgAlY-LDHs nanosheet are as following eventually.